2021
DOI: 10.1158/1078-0432.ccr-21-1656
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib Dose Expansion and Translational Analyses of Olaparib in Combination with Capivasertib in Recurrent Endometrial, Triple-Negative Breast, and Ovarian Cancer

Abstract: Purpose: On the basis of strong preclinical rationale, we sought to confirm recommended phase II dose (RP2D) for olaparib, a PARP inhibitor, combined with the AKT inhibitor capivasertib and assess molecular markers of response and resistance. Patients and Methods: We performed a safety lead-in followed by expansion in endometrial, triple-negative breast, ovarian, fallopian tube, or peritoneal cancer. Olaparib 300 mg orally tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…The ComPAKT trial (NCT02338622) evaluated the combination in patients with advanced solid tumors, of the evaluable patients, 44.6% achieved clinical benefit (RECIST complete/partial response or stable disease ≥4 months), including BRCA1/2 mutant cancers and BRCA1/2 wildtype cancers with or without DDR and PI3K/AKT pathway alterations [ 65 ]. A second study in patients with endometrial, ovarian, and triple-negative breast cancers demonstrated a similar clinical benefit rate of 41% [ 66 ]. Provisional analysis of tumor samples from this study determined that markers of DNA damage checkpoint activation and decreased mTOR activity were associated with response, whereas resistance to the combination was associated with high receptor tyrosine kinase activity levels and mTOR activation [ 66 ].…”
Section: Molecularly Targeted Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ComPAKT trial (NCT02338622) evaluated the combination in patients with advanced solid tumors, of the evaluable patients, 44.6% achieved clinical benefit (RECIST complete/partial response or stable disease ≥4 months), including BRCA1/2 mutant cancers and BRCA1/2 wildtype cancers with or without DDR and PI3K/AKT pathway alterations [ 65 ]. A second study in patients with endometrial, ovarian, and triple-negative breast cancers demonstrated a similar clinical benefit rate of 41% [ 66 ]. Provisional analysis of tumor samples from this study determined that markers of DNA damage checkpoint activation and decreased mTOR activity were associated with response, whereas resistance to the combination was associated with high receptor tyrosine kinase activity levels and mTOR activation [ 66 ].…”
Section: Molecularly Targeted Agentsmentioning
confidence: 99%
“…A second study in patients with endometrial, ovarian, and triple-negative breast cancers demonstrated a similar clinical benefit rate of 41% [ 66 ]. Provisional analysis of tumor samples from this study determined that markers of DNA damage checkpoint activation and decreased mTOR activity were associated with response, whereas resistance to the combination was associated with high receptor tyrosine kinase activity levels and mTOR activation [ 66 ]. The authors conclude that these putative biomarkers could improve patient selection for this combination, although it is unclear whether these markers of resistance were dependent on prior PARPi exposure or varied between malignancies.…”
Section: Molecularly Targeted Agentsmentioning
confidence: 99%
“…The combination was both tolerable and effective, especially in epithelial ovarian cancer (N = 28), with 10 patients (36%) achieving a partial response and 50% showing stable disease [154]. In two phase 1 trials, the combination of olaparib with capivasertib, an AKT inhibitor, demonstrated tolerability and antitumor efficacy in both germline BRCA1/2-mutant and wild-type disease [155,156]. Further studies are ongoing (NCT04729387, NCT03660826) to validate the combination of PI3K-AKT pathway inhibitors and PARP inhibitors in various clinical situations.…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%
“…While combination therapy required a dose attenuation of the pan-PI3Ki BKM120 in one study [ 77 ], the combination of olaparib with the PI3Ki alpelisib was shown to be safe and effective [ 78 ]. Similarly, olaparib combination appeared to be safe with the protein kinase B inhibitor capivasertib [ 79 , 80 ]. Additionally, there were no clinically relevant interactions between olaparib and endocrine therapy including anastrozole, letrozole, or tamoxifen [ 81 ].…”
Section: Olaparibmentioning
confidence: 99%